Timely diagnosis of lysosomal acid lipase deficiency in children and young adults with lipid profile abnormalities. Expert opinion - M.V. Ezhov; E.Yu. Zakharova; A.A. Avramenko; A.S. Alieva; I.N. Zakharova; I.V. Leont'eva; S.I. Malyavskaya; I.M. Osmanov; D.I. Sadykova; M.L. Stolina; T.V. Strokova (LCC «Medicine-Inform», 2021)
M.V. Ezhov1, E.Yu. Zakharova2, A.A. Avramenko3,4, A.S. Alieva5, I.N. Zakharova6, I.V. Leont'eva7, S.I. Malyavskaya8, I.M. Osmanov9, D.I. Sadykova10, M.L. Stolina11, T.V. Strokova7,12 1National Medical Research Center of Cardiology, Moscow, Russian Federation 2Research Center for Medical Genetics, Moscow, Russian Federation 3V.P. Polyakov Samara Regional Clinical Cardiological Dispensary, Samara, Russian Federation 4Samara State Medical University, Samara, Russian Federation 5V.A. Almazov National Medical Research Center, St. Petersburg, Russian Federation 6Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 7Pirogov Russian National Research Medical University, Moscow, Russian Federation 8North State Medical University, Arkhangelsk, Russian Federation 9Z.A. Bashlyaeva Children's City Clinical Hospital, Moscow, Russian Federation 10Kazan State Medical University, Kazan, Russian Federation 11Pacific State Medical University, Vladivostok, Russian Federation 12Federal Research Center for Nutrition and Biotechnology, Moscow, Russian Federation Lysosomal acid lipase deficiency (LAL-D) is a monogenic progressive life-threatening condition characterized by abnormal lipid profiles in most patients of all ages. Timely diagnosis and early pathogenetically-oriented treatment (available in Russia) are crucial for children and young adults since abnormal serum levels of lipids are associated with the onset and severity of atherosclerosis in adolescence, young and middle age. The prognosis of LAL-D without pathogenetically oriented treatment is poor. Data on cholesteryl ester storage disease (a variant of LAL-D in children and adults), early atherosclerosis, coronary heart disease, aortic calcification, etc., are available. However, early diagnosis of LAL-D is difficult due to long-term latent course and nonspecific clinical signs. In December 2020, a panel of leading Russian experts in the diagnosis and treatment of orphan diseases and lipidologists was held in Moscow. This panel developed an algorithm to optimize the early diagnosis of dyslipidemias in children and young adults and identify patients with LAL-D in a total population of patients with lipid profile abnormalities. Keywords: lysosomal acid lipase deficiency, lipid profile, atherosclerosis, lipid center. For citation: Ezhov M.V., Zakharova E.Yu., Avramenko A.A. et al. Timely diagnosis of lysosomal acid lipase deficiency in children and young adults with lipid profile abnormalities. Expert opinion. Russian Journal of Woman and Child Health. 2021;4(3):268-276 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-268-276.